The influence of hormonal replacement therapy on some biophysical properties of skin and subjective self-assessment of the skin condition by women in menopause - Pełka, Marcin; Szczęsny, Dariusz; Kocur, Józef; Broniarczyk-Dyła, Grażyna (Menopause Review/Przegląd Menopauzalny, 2011)
Over time a wide range of changes occur within the skin and make up the phenomenon of its aging. It is a composite, multiform-type process all aspects of which have not been exactly learnt yet. This phenomenon is a comprehensive result of a natural, internal process of aging, mass of UV-radiation dose (photoaging), influence of different environmental factors and also the deficiency of genital hormones, which in the case of women at the age of around 50 is defined as menopause. Hormonal replacement therapy involves supply of feminine genital hormones for minimising of menopause symptoms and prevention of remote consequences. HRT significantly affects subjective self-assessment of the skin condition by women in menopause and changes some biophysical properties of the skin surface. Aims : to demonstrate changes to some biophysical properties of the skin affected by hormonal replacement therapy and compare them with subjective self-assessment of the skin condition by women in menopause. Methods : Measurements of the biophysical properties of skin surface (sebumetry, corneometry, pH-metry, mexa-metry and TEWL); questionnaire of subjective self-assessment of the skin condition by women in menopause. Results : Hormonal replacement therapy affects some biophysical properties of the skin surface. HRT increased the sebum level, water content, decreased erythema of the skin and reduced the transepidermal water loss (TEWL). The level of melanin within skin grows due to the feminine hormone genital application. Subjective self-assessment of the skin condition by women in menopause does not correlate with results of measurements of biophysical properties of the skin surface. Conclusions : Hormonal replacement therapy changes some biophysical properties of the skin surface and considerably improves appearance and functions of the skin of women in menopause. Women using hormonal replacement therapy perceive worse condition of skin in comparison to women without HRT.